Giant among dwarfs: Meganannus lewisi, gen. n. and sp. n., a new genus and species of minute litter bugs from Costa Rica (Hemiptera: Schizopteridae) - Weirauch, Christiane; Whorrall, Kyle; Knyshov, Alexander; Hoey-Chamberlain, Rochelle (Zootaxa, 2018)
The Neotropical biodiversity of the cryptic and tiny minute litter bugs in the family Schizopteridae—although thought to be the best documented tropical fauna of Schizopteridae—is still poorly known. Sixteen species of Schizopteridae have been described from Costa Rica, 13 of which during the past few years, and the last new genus of Schizopteridae from that country was described more than half a century ago. We here describe and document a new monotypic genus of Schizopteridae from Costa Rica, Meganannus n. gen. The new genus belongs to the “Ogeriinae” + Schizopterinae lineage of Schizopteridae and stands out among other litter bugs by the large body size, among other features. We provide habitus photographs and document morphological details using scanning electron, confocal, and light compound microscopic images. A map and measurements are also produced. An illustrated identification key to genus groups and/or genera of Neotropical Schizopteridae including this new genus is presented.